POLA KOMUNIKASI DEPUTI TIGA KEMENTERIAN PEMUDA DAN OLAHRAGA DALAM PENERAPAN KEGIATAN VIRTUAL MEETING DI MASA PANDEMI COVID 19 - Muhammad Javier Marsha (2021)
At the beginning of 2020, Indonesia and also the whole world were faced with the Novel Coronavirus Disease-19 or commonly referred to as the Covid 19 Virus which was finally designated by the World Health Organization (WHO) as a Pandemic on March 11, 2020. The Covid 19 pandemic changed conditions and made the government The Center issued a policy of Large-Scale Social Restrictions (PSBB). The government agency Deputy 3 for Sport Cultivation from the Ministry of Youth and Sports is also involved in implementing work from home (WFH) activities. The use of digital media with virtual communication applications in every activity is commonplace (google meet). The purpose of the study was to determine the communication that occurred within Deputy 3 during a virtual meeting. Research with a descriptive qualitative approach, using interviews as basic data collection, documentation, and in-depth observation. The theory used in the analysis of this research is the theory of Computer Mediated Communication (CMC), in which the CMC theory is related to this research. The results of research from 4 informants who have been interviewed in depth show that communication that occurs during virtual meetings takes place interactively with reciprocal delivery of messages. Communication during virtual meetings runs smoothly (the purpose of communication between the communicator and the communicant is achieved/there is a commonality of meaning), both communication between employees and superiors and fellow employees. There are also obstacles in communicating when conducting virtual meetings, namely due to internet network disturbances. And there are several advantages and disadvantages in the implementation and communication of this virtual meeting.